PENGANGKATAN ANAK SAKIT (BELANGIR) DALAM TRADISI MASYARAKAT BANGKA: KAJIAN HUKUM ISLAM DI DESA SARANGMANDI KECAMATAN SUNGAI SELAN - Duta Argesta; Al Fakhri Zakirman; Ahmad Fadholi (Syaksia: Jurnal Hukum Perdata Islam, 2026)
This study discusses the Islamic legal perspective on the practice of adopting sick children (belangir) in Sarangmandi Village, Sungai Selan District, Central Bangka Regency. The research focuses on the adoption process and the factors underlying the practice. The findings show that this practice is a local tradition carried out when frequently ill children are treated by traditional healers through prayers, massage, and herbal remedies, after which the children are adopted by the healer. From the perspective of Islamic law, this practice is permissible as long as it does not sever the child’s lineage (nasab) from their biological parents. The adoption is based on mutual help and the welfare of the child and does not contradict the teachings of the Qur’an and Hadith. Therefore, this customary practice can be accepted as it is in accordance with the principles of Islamic law.